Redescription of the monotypic genus Scelidomachus Pocock, 1899 (Aranei: Palpimanidae) and its type species - Sergei L. Zonstein; Yuri M. Marusik; Mikhail M. Omelko (KMK SCIENTIFIC PRESS LTD, MOSCOW STATE UNIV, 2022)
Scelidomachus socotranus Pocock, 1899, the type species of Scelidomachus Pocock, 1899 is redescribed based on the holotype and paratype males from Socotra. The genus is rediagnozed.